Political awareness and microtargeting of voters in electoral competition - Burkhard C. Schipper; Hee Yeul Woo (University of California, Department of Economics, 2012)
In modern elections, ideologically motivated candidates with a wealth of information about individual voters and sophisticated campaign strategies are faced by voters who lack awareness of some political issues and are uncertain about the exact political positions of candidates. This is the context in which we analyze electoral competition between two ideologically fixed candidates and a finite set of voters. Each political issue corresponds to a dimension of a multidimensional policy space in which candidates' and voters' most preferred policy points are located. Candidates can target messages to subsets of voters. A candidate's message consists of a subset of issues and some information on her political position in the subspace spanned by this subset of issues. The information provided can be vague, it can be even silent on some issues, but candidates are not allowed to bluntly lie about their ideology. Every voter votes for the candidate she expects to be closest to her but takes into account only the subspace spanned by the issues that come up during the campaign. We show that any prudent rationalizable election outcome is the same as if voters have full awareness of issues and complete information of policy points, both in parliamentary and presidential elections. We show by examples that these results depend on the strength of electoral competition, the ability to target information to voters, and the political reasoning abilities of voters.
Keywords: C72; D71; P16; 330; electoral competition; multidimensional policy space; microtargeting; dog-whistle politics; ideological candidates; verifiable information; unawareness; framing; prudent rationalizability; forward-induction